1977
DOI: 10.1056/nejm197707142970205
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the Race and Economic Status of Patients and Who Performs Their Surgery

Abstract: We evaluated the relation between race and economic status of surgical patients and their likelihood of being treated by a surgeon in training rather than by a staff surgeon. Blacks were 2.2 to 4.3 times more likely than whites to be under the care of surgeons in training (P less than 0.001). This relation has remained unchanged over the past two decades. It remained when the method of payment was via self-payment or private insurance, but disappeared when patients being paid for by Medicaid were considered. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 1 publication
0
17
0
1
Order By: Relevance
“…Organizational segregation of care represents a type of between difference within the same organization. Nearly 40 years ago, Egbert & Rothman reported that blacks with private insurance or Medicare were more likely to be operated on by residents than by attending surgeons within the same hospital (42). Today, black, Hispanic, and Asian patients are more likely to be operated on by senior residents than by attending surgeons operating alone.…”
Section: Principle 6 Differences Between and Within Geographic Areasmentioning
confidence: 99%
“…Organizational segregation of care represents a type of between difference within the same organization. Nearly 40 years ago, Egbert & Rothman reported that blacks with private insurance or Medicare were more likely to be operated on by residents than by attending surgeons within the same hospital (42). Today, black, Hispanic, and Asian patients are more likely to be operated on by senior residents than by attending surgeons operating alone.…”
Section: Principle 6 Differences Between and Within Geographic Areasmentioning
confidence: 99%
“…For example, placement on kidney 0952-8180/$ -see front matter D 2006 Elsevier Inc. All rights reserved. doi:10.1016/j.jclinane.2005.08.006 transplant waiting lists, recommendation for cardiac surgery, pain management for cancer and long bone fractures, treatment options for prostate cancer, and psychiatric problems are affected by these and other nonmedical factors [1][2][3][4][5][6][7][8]. This phenomenon remains largely unstudied in the field of anesthesiology.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] As recently as 1977, black surgical patients at the Johns Hopkins Hospital, Baltimore, Maryland, were 2 to 4 times more likely than white patients to undergo a cholecystectomy or hernia repair by a surgeon in training rather than by an attending surgeon. 8 Although overt displays of racism have diminished, racial disparities in the quality of care persist. These disparities, in turn, may contribute to significant racial differences in mortality and morbidity across a range of health conditions.…”
mentioning
confidence: 99%